The role of satisfaction when mediating loyalty: What’s for in online tourism purchases? - Pereira, H.; Salgueiro, M. F. (EURAM 2020 Conference Proceedings, 2020)
The online market draws attention from the tourism industry due to its important evolution and, nowadays, to its substantial dimension. The main objectives of this paper are: 1) to investigate the influence of four relationship marketing dimensions on online tourism customer satisfaction – customer needs, service quality, interactive marketing and personalization; 2) to analyze the mediating effect of e-satisfaction level, on the relation between these determinants and the formation of loyalty. A questionnaire was applied to a sample of 3188 regular online buyers of the national leader in the tourism sector. The statistical analyses were conducted within the Structural Equation Modeling framework. The most important results have shown that there are three dimensions of relationship marketing that significantly influence e-customer satisfaction – understanding customer needs, service quality and personalization. Results also show that there is a complete mediating effect of e-customer satisfaction in the relationship between the relationship marketing dimensions and e-customer loyalty. Thus, research results provide an important insight into how e-companies can pursuit and use delight to highlight customers’ loyalty and, with this, to improve their competitive edge. These results allow for a better understanding of customer specificities, with practical actions aimed at their real needs and expectations.